2006
DOI: 10.1096/fj.05-5709com
|View full text |Cite
|
Sign up to set email alerts
|

Causative role of oxidative stress in a Drosophila model of Friedreich ataxia

Abstract: Friedreich ataxia (FA), the most common form of hereditary ataxia, is caused by a deficit in the mitochondrial protein frataxin. While several hypotheses have been suggested, frataxin function is not well understood. Oxidative stress has been suggested to play a role in the pathophysiology of FA, but this view has been recently questioned, and its link to frataxin is unclear. Here, we report the use of RNA interference (RNAi) to suppress the Drosophila frataxin gene (fh) expression. This model system parallels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
135
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 66 publications
10
135
1
Order By: Relevance
“…In an earlier study with our Drosophila FRDA model (17), we showed that widespread RNAi-mediated DFH deficiency with the ubiquitous Gal4 driver, daG 32 , caused delayed metamorphosis, impaired eclosion, and severe early mortality of the few surviving adults, and that overexpression of SOD1, SOD2, or CAT by the daG 32 -Gal4 driver did not improve the capacity of DFH-deficient larvae to develop into adults. In the present work, we have focused DFH deficiency on the adult PNS, which spares preadult effects, leaving reduced adult life span as the predominant phenotype.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In an earlier study with our Drosophila FRDA model (17), we showed that widespread RNAi-mediated DFH deficiency with the ubiquitous Gal4 driver, daG 32 , caused delayed metamorphosis, impaired eclosion, and severe early mortality of the few surviving adults, and that overexpression of SOD1, SOD2, or CAT by the daG 32 -Gal4 driver did not improve the capacity of DFH-deficient larvae to develop into adults. In the present work, we have focused DFH deficiency on the adult PNS, which spares preadult effects, leaving reduced adult life span as the predominant phenotype.…”
Section: Discussionmentioning
confidence: 89%
“…That overexpression of the H 2 O 2 -scavenging enzyme, CAT, restores the short life span of DFH-deficient Drosophila strongly implicates H 2 O 2 as a critical element in the mechanism responsible for this early adult mortality phenotype. Although CAT provides robust restoration of life span in DFH-deficient flies, the disruption of iron metabolism arising from DFH deficiency should also occur in the mitochondrial matrix where DFH also resides (17,32) and where mitochondrial superoxide emanating from the respiratory chain is reduced to H 2 O 2 by SOD2 (33). In other words, all of the reactants for the generation of hydroxyl radical via Fenton chemistry should be present in the mitochondrial matrix of DFH-deficient flies, and enhanced scavenging of H 2 O 2 in the mitochondrial matrix should equal or surpass that in the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When these activities were restored, the activities of several iron-sulfur-containing enzymes were also recovered, suggesting that ironsulfur deficiency in ⌬yfh1 yeasts is due to the lack of SOD activities. In frataxin-deficient Drosophila melanogaster, aconitase deficiency is observed only under hyperoxia conditions (19), whereas H 2 O 2 scavenging restores aconitase activity (20). All of these observations suggest that lack of iron-sulfur enzymatic activities in frataxin-deficient cells could be a consequence of oxidative stress conditions generated by iron accumulation.…”
mentioning
confidence: 95%